New geochemical and Sr-Nd-Hf isotopic constraints on the genesis of kimberlites and ultramafic lamprophyres from the Adelaide Fold Belt and Gawler Craton, South Australia - Hayden Dalton; Andrea Giuliani; Angus Fitzpayne; Bradley J. Peters (Mineralogy and Petrology, 2025)
This study investigates the geochemical and isotopic characteristics of Jurassic kimberlites and ultramafic lamprophyres (UMLs) from four clusters within the Adelaide Fold Belt (AFB) and two within the Gawler Craton in South Australia. Petrographic analysis, including the occurrence of magmatic clinopyroxene in the groundmass, supported by a review of available mica and spinel compositional data, indicates that many previously classified kimberlites (Eurelia, Angaston and Terowie) are, in fact, ultramafic lamprophyres. New whole-rock major-, trace element and Sr-Nd-Hf isotopic results, augmented by in-situ perovskite and carbonate Sr isotopes, reveal that this sample suite exhibits extensive geochemical variability. These new data highlight the significant role of crustal contamination in modifying not only bulk-rock major, trace element and Sr isotope systematics, the latter being pristine exclusively in low-SiO 2 samples, but also Nd and Hf isotopic signatures. This is most evident for the Mount Hope (εNd (i) = -5.1 to -1.5; εHf (i) = -8.6 to -2.7) and Cleve (εNd (i) = -3.7 to -0.2; εHf (i) = -6.6 to +0.3) kimberlites of the Gawler Craton which display geochemically enriched compositions that are rarely seen in kimberlitic rocks. In contrast, the AFB samples exhibit less inter-sample isotopic variability and have compositions that are more typical of kimberlites and UMLs globally (εNd (i) = +0.3 to +3.9; εHf (i) = +0.7 to +6.6). There is no clear lithospheric thickness control governing the absence of UMLs on the Gawler Craton and their presence within the AFB. Similarly, there are no systematic differences in Sr–Nd-Hf isotopes between uncontaminated kimberlites and UMLs, arguing against obvious differences in their asthenospheric sources. We tentatively suggest that contribution by more pervasively metasomatised lithospheric mantle beneath the AFB compared to the Gawler craton (based on existing garnet xenocryst data) may facilitate the formation of ultramafic lamprophyres in this region. While subduction along the southern palaeo-margin of Pangea likely did not directly trigger magmatism, it may have facilitated deep mantle upwelling linked to the contemporaneous Karoo-Ferrar Large Igneous Province, with related formation of kimberlites and UMLs in South Australia.

The Cambrian post-orogenic A-type granitoids from SE Brazil: metasomatized lithospheric mantle sources, crystal fractionation and minor crustal assimilation - Clara Talca Onken; Andrea Galli; Andrea Giuliani; Angus Fitzpayne; Bradley J. Peters; Valdecir A. Janasi; Max W. Schmidt (Contributions to Mineralogy and Petrology, 2025)
The role of mantle vs. crustal contributions to A-type granitoids are heavily debated, in line with the wide compositional diversity among these magma types. The Cambrian post-orogenic Venda Nova and Várzea Alegre Plutons of the Araçuaí belt, SE Brazil, turn out to represent an endmember case where the clear “crustal” isotopic signature is already present in the primitive mantle melts and hence mantle source. The mildly alkaline Venda Nova Pluton comprises wehrlites, gabbronorites, diorites, quartz syenites and titanite granites with mineral (clinopyroxene, amphibole, apatite) and bulk rock age-corrected εNd (500 Ma) values of -11.8 to -9.5 and 87 Sr/ 86 Sr (500 Ma) values of 0.7069–0.7080. The more calc-alkaline Várzea Alegre Pluton comprises gabbronorites, monzodiorites, charnockites, and monzo- and syeno-granites with mineral and bulk rock εNd (500 Ma) of -10.1 to -7.6 and 87 Sr/ 86 Sr (500 Ma) of 0.7067–0.7079 in the gabbronorites, but more variable values (0.7075–0.7097) in the charnockites and granites. Mixing models between the Venda Nova gabbronorites and potential crustal assimilants, combined with a mineral fractionation model, show that granite genesis primarily resulted from crystal fractionation from gabbronoritic melts with little crustal assimilation. For Várzea Alegre, the greater scatter in εNd points to a more heterogeneous mantle source, while the larger range of 87 Sr/ 86 Sr points to some localized assimilation of country rock metapelites or S-type granitoids. In both cases, the least differentiated gabbroic rocks already show geochemically enriched isotopic signatures which lack corresponding crustal compositions in the Araçuaí belt. We attribute this crustal signature to a lithospheric mantle source that was metasomatized both in ancient times to generate strongly negative Nd isotopes and more recently by fluids/melts related to subduction along the ~ 600 Ma Rio Doce arc, now incorporated into the Araçuaí belt. This contribution highlights that apparently “crustal” isotopic signatures in A-type granitoids can be derived from metasomatic enrichment of the lithospheric mantle rather than crustal assimilation.

Major-, trace-element and Sr-Nd-Hf isotope geochemistry of diamondiferous dykes from Tonguma and Koidu, Sierra Leone: Highly micaceous kimberlites formed by assimilation of metasomatised lithospheric mantle rocks - Angus Fitzpayne; Andrea Giuliani; Geoffrey H. Howarth; Bradley J. Peters; Manuela A. Fehr; Roland Maas (Chemical Geology, 2023)

Kimberlite-related metasomatism recorded in MARID and PIC mantle xenoliths - Angus Fitzpayne; Andrea Giuliani; David Phillips; Janet Hergt; Jon D. Woodhead; James Farquhar; Marco L. Fiorentini; Russell N. Drysdale; Nanping Wu (Mineralogy and Petrology, 2018)